Weniger Lohn, mehr Beschäftigung? Ein Standpunkt - Oliver Nikutowski; Florian Schwimmer (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2004)
– In this paper an alternative view of the relation between the wage level, wage dispersion, training incentives and employment is presented. We provide some theoretical arguments which cast doubt on the standard thesis that unemployment - especially in Germany - is mainly caused by labor market institutions and excessive wages. Rather there are several indications that a persistent lack of demand is responsible for the major part of the German unemployment problem.
urn:nbn:de:bvb:19-epub-426-8
Keywords: J24; J31; J68; 330; wage dispersion; wage level; on-the-job training; unemployment; competitiveness; Lohnniveau; Lohnspreizung; Ausbildung; Arbeitslosigkeit; Wettbewerbsfähigkeit